Kalsium Oksida Berbasis Limbah sebagai Katalis Heterogen pada Sintesis Biodiesel dari Minyak Goreng Bekas - Haryono (Retii, 2022)
Biodiesel, which is a methyl ester of fatty acids, has been considered as a renewable fuel that is environmentally friendly because it is able to support the sustainability of the carbon dioxide cycle. Biodiesel is conventionally synthesized from oil or fat with a homogeneous base catalyst, such as potassium hydroxide or sodium hydroxide. However, the use of homogeneous catalysts has several drawbacks, such as: it requires a tight free fatty acid content, is prone to oil saponification reactions, is relatively difficult to separate, and cannot be regenerated. Therefore, heterogeneous catalysts in biodiesel synthesis are considered as a substitute for homogeneous catalysts. Calcium oxide is a solid heterogeneous catalyst that has been proven effective in assisting the transesterification reaction of oil into biodiesel. Calcium oxide can be synthesized from calcium carbonate, which is widely found in waste, such as blood clam and egg shells. This study aims to synthesize and characterize calcium oxide from egg and crab shells as a catalyst in the synthesis of biodiesel from used cooking oil. Calcium oxide was obtained by calcination to blood clam and egg shells at 800 oC for 8 hours. The calcination results were further characterized by the method of x-ray diffraction and BET (Brunauer-Emmet-Teller) isotherm adsorption-desorption to determine the type of oxide phase formed and the surface characterization. The synthesis of biodiesel was carried out at a reaction time of 2 hours, a temperature of 60 oC, a molar ratio of oil to methanol 1:12, and a catalyst content of 10%. The results showed that calcium oxide was successfully synthesized from blood clam and egg shells waste with different characteristics. Calcium oxide from the two wastes is able to catalyze the transesterification reaction of used cooking oil into biodiesel, and biodiesel is produced according to SNI 7182-2015 concerning biodiesel quality standards. Keyword: biodiesel, calcium oxide, blood clam, egg, transesterificatio